The Effect of Baffle Spiral on The Performance of Heat Exchanger - Adi Pratama Putra; Ikhwanul Qiram (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
The application of heat exchanger still causes many problems. Research on the performance improvement of the heat exchanger is also conducted by adding baffle. This research is aimed at finding out the influence of spiral baffle on the performance of heat exchanger. Research is conducted by doing experiment. The heat exchanger used is the opposite flow type. The independent variable includes round and triangular springs with gap spacing of 1, 2 and 3 cm which are installed in the heat pipe. The flow rate of the water is varied by 100, 150, 200 and 250 ml / sec. The dependent variable includes the temperature of hot water (in and out) and the temperature of cold water (in and out). Temperature measurement is done by using a K type thermocouple every minute for 5 minutes. Discharge measurement is done by using flow meter and stopwatch. The results showed that there were effects of the spiral and water discharge variation on the rate of heat transfer. The phenomenon of water discharge is inversely proportional to the rate of temperature change. Maximum heat temperature displacement occurred at a variation of 1.5 cm with a flow rate of 31.25 was 1.44o. The minimum heat transfer temperature occurred at a variation of 0.5 cm with a flow rate of 38.46 was 0.82o. The maximum cold temperature heat transfer occurred at a variation of 1.5 cm with a flow rate of 31.25 was 0.52o and the minimum occurred at variation of 0.5 cm with a flow discharge of 38.46 was 0.14o.